New herb gall wasps (Hymenoptera: Cynipidae: Aulacideini) from Kyrgyzstan, with description of a new genus and a review of the genus Panteliella Kieffer, 1901 - Nastasi, Louis F.; Deans, Andrew R. (Zootaxa, 2024)
We describe three new aulacideine herb gall wasp species (Hymenoptera: Cynipidae: Aulacideini) from Kyrgyzstan, a country from which only two Aulacideini species were previously known. One of our new species represents a new genus, which we describe here as Soparia oshensis Nastasi gen. and sp. nov. We describe Panteliella rugosa Nastasi sp. nov., representing a new genus record for Kyrgyzstan. To further facilitate species recognition in Panteliella, we redescribe the genus and the species P. fedtschenkoi; provide a translated description of P. bianchii Vyrzhikovskaya, 1962; comment on complications affecting this genus; and provide a key to Panteliella species. Lastly, we describe Isocolus barakus Nastasi sp. nov., a species with morphology atypical of Isocolus. We provide a key to the Kyrgyz genera of Aulacideini to ensure that they remain diagnosable for future study. Our findings illustrate the continued unveiling of a diverse herb cynipid fauna in Central Asia and a need for further taxonomic study in the region.